Mechanisms of low susceptibility to the disinfectant benzalkonium chloride in a multidrug-resistant environmental isolate of Aeromonas hydrophila - Chacón Jiménez, Luz María (2023)
Excessive discharge of quaternary ammonium disinfectants such as benzalkonium chloride (BAC) into aquatic systems can trigger several physiological responses in environmental microorganisms. In this study, we isolated a less-susceptible strain of Aeromonas hydrophila to BAC, designated as INISA09, from a wastewater treatment plant in Costa Rica. We characterized its phenotypic response upon exposure to three different concentrations of BAC and characterized mechanisms related to its resistance using genomic and proteomic approaches. The genome of the strain, mapped against 52 different sequenced A. hydrophila strains, consists of approximately 4.6 Mb with 4,273 genes. We found a massive genome rearrangement and thousands of missense mutations compared to the reference strain A. hydrophila ATCC 7966. We identified 15,762 missense mutations mainly associated with transport, antimicrobial resistance, and outer membrane proteins. In addition, a quantitative proteomic analysis revealed a significant upregulation of several efflux pumps and the downregulation of porins when the strain was exposed to three BAC concentrations. Other genes related to membrane fatty acid metabolism and redox metabolic reactions also showed an altered expression. Our findings indicate that the response of A. hydrophila INISA09 to BAC primarily occurs at the envelop level, which is the primary target of BAC. Our study elucidates the mechanisms of antimicrobial susceptibility in aquatic environments against a widely used disinfectant and will help better understand how bacteria can adapt to biocide pollution. To our knowledge, this is the first study addressing the resistance to BAC in an environmental A. hydrophila isolate. We propose that this bacterial species could also serve as a new model to study antimicrobial pollution in aquatic environments.